HIV viral suppression in Oman: Encouraging progress toward achieving the United Nations 'third 90'. (June 2018) - Elgalib, Ali; Shah, Samir; Al-Habsi, Zeyana; Al-Fouri, Maha; Al-Sawafi, Halima; Al-Noumani, Jalila; Al-Baloushi, Adil; Al-Alawi, Saad; Al-Badi, Salma; Mohammed, Zainab; Al-Ghafri, Jokha; Suleimani, Asma; et al.
Highlights: Capacity-building interventions introduced by the Oman National AIDS Programme have improved the quality of HIV care. More patients achieved HIV viral load suppression in 2017 compared to baseline levels from 2015. Fewer patients were lost to follow-up in 2017 compared to those disengaged from care in 2015. Abstract: Objective: To assess the impact of capacity-building interventions introduced by the Oman National AIDS Programme on the quality of HIV care in the country. Methods: HIV viral load (VL) suppression and loss to follow-up (LTFU) rates were calculated for the period before (in December 2015; n  = 1098) and after (in June 2017; n  = 1185) the introduction of the interventions: training, support, and care pathway development. Three HIV VL cuts-offs at last measurement in the year of interest were used to define VL suppression. Results: In the intention-to-treat (ITT) analysis, rates of VL <200 copies/ml and <1000 copies/ml increased from 51.9% in 2015 to 65.5% in 2017 (relative risk (RR) 1.26, 95% confidence interval (CI) 1.17–1.36) and from 58.1% in 2015 to 70.9% in 2017 (RR 1.22, 95% CI 1.14–1.30), respectively; p <  0.0001 for both. Similarly, in the on-treatment analysis, rates of VL <200 copies/ml and <1000 copies/ml increased from 64.2% in 2015 to 76.9% in 2017 (RR 1.20, 95% CI 1.12–1.28) and from 71.9% in 2015 to 83.2% in 2017 (RR 1.16, 95% CI 1.10–1.22), respectively. Fewer patients were LTFU in 2017 than in 2015 (14.7% (157/1061) vs. 19.2% (188/981); RR 0.77, 95% CI 0.64–0.94). Conclusions: Achieving the UNAIDS target of 90% of HIV patients on treatment having VL suppression by 2020 is feasible in Oman.